INNOVATION OF WATER HYACINTH-BASED HANDICRAFTS: A STRATEGY FOR COMMUNITY ECONOMIC ENHANCEMENT IN BANJARMASIN - Nor, Baseran; Kurniansyah, Kurniansyah; Abdillah, Muhammad; Nabila, Rizqah; Khadijah, Retno Salsabila (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Lambung Mangkurat, 2025)
Banjarmasin, frequently referred to as the